Knowledge of safe injection practices, prevention of sharp injuries, and medical wastemanagement in Nursing students of the University of Medicine and Pharmacy at Ho ChiMinh City (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: To describe the knowledge regarding safe injection practices, prevention of sharp injuries and medical waste management in Nursing students of the University of Medicine and Pharmacy at Ho Chi Minh City.Method: A cross-sectional study conducted in 264 Nursing students, during the academic year 2022-2023. A pre-designed questionnaire was used to survey knowledge regarding standard precautions.Results: The study found that 51% of nursing students possessed accurate knowledge regarding safe injection practices and the prevention of injuries from sharp objects. Notably, the aspect concerning contact precautions for managing wounds in HIV/AIDS patients had the highest correct response rate at 92.1%. Additionally, 73% of nursing students demonstrated correct knowledge about medical waste management, with the highest accuracy (93.2%) in the area of waste segregation at the point of generation.Conclusion: Overall, more than half of the students have correct knowledge about safe injection practices, prevention of sharp injuries, and medical waste management in standard precautions (all above 50%).